2021
DOI: 10.1155/2021/6550809
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization Methods in the Submerged Arc Discharge Synthesis of Carbon Nanostructures

Abstract: Many papers, in which the submerged arc discharge (SAD) method in nanoparticle synthesis was used, reported similar operating parameters, but different electrode erosion rate values, different yields and purities of the obtained nanostructures, and a different sort of contaminants present in the synthesis. Analyzing these articles, we found insufficient attention to ensure the arc power stability, which is a key factor guaranteeing the product homogeneity and quality. This paper presents an analysis of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Therefore, the amount of solid in the supernatant and precipitate was larger, when compared to this work. A detailed analysis of these processes can be found in [10,15]. Overall, it was shown that the use of a stabilisation system can The determination of the yield was carried out at 30 A as it was considered optimal for the synthesis of CNSs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the amount of solid in the supernatant and precipitate was larger, when compared to this work. A detailed analysis of these processes can be found in [10,15]. Overall, it was shown that the use of a stabilisation system can The determination of the yield was carried out at 30 A as it was considered optimal for the synthesis of CNSs.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, arc power stability is crucial in SADW synthesis to ensure the homogeneity and quality of produced CNSs. In almost all published works on SADW, appropriate systems for arc stabilisation are not used [10]. In most studies, arc stability evaluation is based solely on the intensity of emitted arc light or other unsuitable indicators [11].…”
Section: Introductionmentioning
confidence: 99%
“…[32] CDs were first discovered accidentally by Xuan co-workers, during the electrophoretic purification of carbon nanotubes and since then, their research activity in this area has been increasingly active. [36,37] Despite the fact that the mechanism of CDs fluorescence is still under debate, there are certain hypotheses comprising the emission through defects and the fluorescence from conjugated moieties within the nanoparticle, which are two explanations for their luminescent behavior. [38] Nevertheless, such fluorescent properties may likely arise from a combined effect of multiple mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanoparticles (CNPs) exist of various kinds, including Carbon Dots (CDs) [32] Carbon Nanoonions (CNO), [34] carbon nanotubes (CNT) [35] and polyhedral nanoparticles [32] . CDs were first discovered accidentally by Xuan co‐workers, during the electrophoretic purification of carbon nanotubes and since then, their research activity in this area has been increasingly active [36,37] . Despite the fact that the mechanism of CDs fluorescence is still under debate, there are certain hypotheses comprising the emission through defects and the fluorescence from conjugated moieties within the nanoparticle, which are two explanations for their luminescent behavior [38] .…”
Section: Introductionmentioning
confidence: 99%
“…Instabilities in carbon discharges, detectable as oscillations in arc voltage and optical emission, have been related to the particular geometries of ablating anode (Gershman and Raitses 2016, Yatom et al 2017b). Even submerged arcs show instable behaviour (Sano et al 2003, Bhattacharya et al 2019, Hernandez-Tabares et al 2021…”
mentioning
confidence: 99%